High prevalence of human papillomavirus infection in sinonasal inverted papilloma: a single‐institution cohort of patients. Issue 5 (27th February 2020) - Frasson, Giuliana; Cesaro, Sonia; Cazzador, Diego; Traverso, Giulia; Emanuelli, Enzo; Borsetto, Daniele; Munari, Giada; Salmaso, Roberta; Martini, Alessandro; Boscolo‐Rizzo, Paolo; Rugge, Massimo
Abstract : Background: Both the prevalence of sinonasal inverted papilloma (IP) and the causal association with alpha‐human papillomaviruses (alpha‐HPVs) are controversial. In this study we aimed to determine HPV status in histologically selected, microdissected, formalin‐fixed, and paraffin‐embedded tissue samples of IP. Methods: HPV status was assessed retrospectively by polymerase chain reaction (PCR)‐bead‒based multiplex genotyping on tissue samples of patients diagnosed with IP and consecutively treated with endoscopic resection. Forty‐one HPV genotypes were considered, distinguishing between high risk and low risk. HPV status was correlated with demographics and clinical variables. Sixty sinonasal IP tissue samples were initially considered. After exclusion of 5 cases due to insufficient quality/quantity of the samples, 55 patients were included for analysis. Results: HPV‐DNA sequences were identified in 34 of 55 (61.8%) IPs, with a higher prevalence of high‐risk than low‐risk HPV genotypes (19 [55.9%] and 15 cases [44.1%], respectively). HPV16 strongly prevailed among the high‐risk HPV cases (84.2%), and HPV54 prevailed among the low‐risk HPV cases (53.3%). IPs with origin within the maxillary sinus were significantly associated with high‐risk HPV ( p = 0.019). No significant associations emerged between HPV status and demographics or clinical variables. Conclusion: In a series of 55 IP tissue samples, HPV‐DNA sequences were identified in 61.8% of cases, which differs from the data of previous investigations. Further case‐control studies are advocated to confirm this prevalence in the Italian population addressed, and also to clarify any pathogenic involvement of HPV in the natural history of IPs.